Collective intelligence in agricultural production units. Case study: Central Eastern Region of Costa Rica” - Salazar Calderón, Mayrin (2024)
The agricultural sector is of great importance for Costa Rica since it is one of the main exporters and generators of employment. Sometimes agricultural producers join to form the so-called productive units, which bring multiple benefits. For the subsistence of these units, it is important to improve collective intelligence, which is defined as the ability of a group to solve problems and at the same time strengthen the bonds of cohesion in the group. The objective of this research was to determine the factors of collective intelligence that influence agricultural production units in the Central Eastern Region of Costa Rica. This study is qualitative, exploratory, and descriptive in scope. The methodological design applied was the case study, whose sampling framework was constructed based on the PAO 2020 of the Ministry of Agriculture and Livestock. The data collection technique was the in-depth interview and the Atlas.ti software was used for data analysis. The results allow us to identify the genome of collective intelligence present in the units studied, which is oriented towards collaborative work, decision-making by consensus and respect for hierarchy. In addition, although the interest in becoming a member is based on economic goals, the reality is that their actions are directed towards the wellbeing of the collective. The practical implications of this study are important for decision-makers, since it will allow them to orient support to the sector in technical aspects that are important for it; it will also strengthen the collective.Keywords:Costa Rican agricultural sector, agricultural production units, collective intelligence, collective intelligence genome, collaborative work